DNA methylation, inflammation and cancer - Pfeifer, Gerd (Henry Stewart Talks, 2010)
DNA methylation in cancer in general, Lung cancer, Intestinal cancer, Inflammation, Method for genome-wide DNA methylation profiling, Association of the Polycomb complex with DNA methylation in inflammation and cancer
Reviewed at 2020/05/01